Isolation and Identification of a Biologically Active Isoflavonoid from Cudrania javanensis - R. K. Sharma, G. K. Sarmah* and (Journal of Phytology, 2010)
Â SUMMARY Isolation of isoflavonoids has become a frequent endeavor, due to their interesting biological activities. Osajin, 1 (5-hydroxy-3-(3-hydroxyphenyl)-8,8 dimethyl-6-(3-methylbut-2-enyl)-4H.8H-pyrano[2,3-h]chromen-4-one] is a naturally occurring isoflavonoid which was isolated from the fruits of Cudrania javanensis1, 2. The structure was elucidated using spectroscopic methods, including NMR, IR, and MS. Key words: Cudrania javanensis, Moraceae, Isoflavonoids, OsajinÂ <span style="font-weight: normal; font-size: 7pt; line-height: 110%; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-variant: normal! important; mso-fareast-language: EN-SG; mso-font-kerning: 0pt; mso-no-proof: no; mso-ansi-language: EN-SG;" lang="EN-SG">G. K. Sarmah and R. K. Sharma. Isolation and Identification of a Biologically Active Isoflavonoid from Cudrania javanensis. J Phytol 2/5 (2010) 47-49. <span style="font-weight: normal; font-size: 7pt; line-height: 110%; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-variant: normal! important; mso-fareast-language: EN-SG; mso-font-kerning: 0pt; mso-no-proof: no; mso-ansi-language: EN-SG;" lang="EN-SG">*Corresponding Author, Email: gsarmah@yahoo.com <span style="font-size: 7pt; line-height: 110%; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; mso-fareast-font-family: SimSun; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG; mso-bidi-font-family: ’Times New Roman’; mso-bidi-language: AR-SA;" lang="EN-SG">